Expanding and Testing a Latinx Differential Coercion and Social Support Theory of Crime - Curry, Theodore R. (Journal of interpersonal violence, 2023)
We develop and test an extension of differential coercion and social support (DCSS) theory focused on Latinx individuals that employs measures of coercion and social support, both at the individual and environmental levels, that may be especially salient to this population. Data come from Latinx adults (n=863) randomly sampled from El Paso County, Texas and were analyzed using logistic and OLS regression analyses and employed the PROCESS Macro for assessing mediating relationships. Findings show moderate support for hypotheses. Specifically, a structural measure of social support (neighborhood social support) was inversely associated with family violence and mediated relationships between three separate measures of coercion and family violence, supporting predictions. However, two cultural measures of social support (enculturation to Mexico and familismo) did not demonstrate such relationships, failing to support predictions. Additional findings show that two of the three measures of coercion (neighborhood crime and disorder and police harassment) were inversely associated with family violence as predicted, but that a third measure, acculturation to the U.S., was not. Implications for DCSS theory and criminal offending for Latinx are discussed.